Predator responses to fire: A global systematic review and meta‐analysis. Issue 4 (28th January 2020) - Geary, William L.; Doherty, Tim S.; Nimmo, Dale G.; Tulloch, Ayesha I. T.; Ritchie, Euan G.
Abstract: Knowledge of how disturbances such as fire shape habitat structure and composition, and affect animal interactions, is fundamental to ecology and ecosystem management. Predators also exert strong effects on ecological communities, through top‐down regulation of prey and competitors, which can result in trophic cascades. Despite their ubiquity, ecological importance and potential to interact with fire, our general understanding of how predators respond to fire remains poor, hampering ecosystem management. To address this important knowledge gap, we conducted a systematic review and meta‐analysis of the effects of fire on terrestrial, vertebrate predators world‐wide. We found 160 studies spanning 1978–2018. There were 36 studies with sufficient information for meta‐analysis, from which we extracted 96 effect sizes (Hedges' g ) for 67 predator species relating to changes in abundance indices, occupancy or resource selection in burned and unburned areas, or before and after fire. Studies spanned geographic locations, taxonomic families and study designs, but most were located in North America and Oceania (59% and 24%, respectively), and largely focussed on felids (24%) and canids (25%). Half (50%) of the studies reported responses to wildfire, and nearly one third concerned prescribed (management) fires. There were no clear, general responses of predators to fire, nor relationships with geographic area, biome or life‐history traits (e.g. body mass, hunting strategy and diet). Responses varied considerably between species. Analysis of species for which at least three effect sizes had been reported in the literature revealed that red foxes Vulpes vulpes mostly responded positively to fire (e.g. higher abundance in burned compared to unburned areas) and eastern racers Coluber constrictor negatively, with variances overlapping zero only slightly for both species. Our systematic review and meta‐analysis revealed strong variation in predator responses to fire, and major geographic and taxonomic knowledge gaps. Varied responses of predator species to fire likely depend on ecosystem context. Consistent reporting of ongoing monitoring and management experiments is required to improve understanding of the mechanisms driving predator responses to fire, and any broader effects (e.g. trophic interactions). The divergent responses of species in our study suggest that adaptive, context‐specific management of predator–fire relationships is required. Abstract : The authors' paper is the first study that attempts to understand how vertebrate predators are affected by fire across the globe. They found that responses are variable, with ecosystem context likely influencing how predators respond to fire.